The influence of motivation and human resource development on employee performance at the Sendana Subdistrict Office in Majene Regency - Aco Lamama (Pustaka Digital Indonesia, 2023)
This research project, conducted at the Sendana Subdistrict Office in Majene Regency, aims to delve into critical aspects of employee performance within this administrative setting. The primary objectives encompass a comprehensive analysis of the impact of motivation and human resource development on the performance of employees. Motivation has long been recognized as a vital factor influencing employee performance. It's widely believed that motivated employees tend to be more engaged, productive, and committed to their tasks. However, the findings of this study, based on rigorous quantitative analysis using SPSS, indicate that motivation, as a standalone factor, does not exert a significant influence on employee performance within the Sendana Subdistrict Office. Contrastingly, the study reveals a noteworthy relationship between human resource development and employee performance. This suggests that investments in enhancing the skills, knowledge, and capabilities of employees can significantly boost their performance levels. The evidence from the research underscores the importance of ongoing training, skill development, and career advancement opportunities for employees in a government office setting. In summary, while motivation alone may not be the key driver of employee performance in this context, human resource development emerges as a dominant variable. These findings have substantial implications for policymakers and administrators seeking to optimize the performance of government office employees in Majene Regency. The study highlights the importance of investing in the growth and development of human resources to achieve higher levels of performance and efficiency within the Sendana Subdistrict Office.